The Nature of the Administrative Relationships between the Shariʿah Board and the Stakeholders in Brunei Darussalam - Hassan, Mazin; Besar, Azrin; Jaidin, Halida (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2023)
Corporate governance involves a set of administrative relationships between a company and other stakeholders. The shareholders and management should take part in protecting the interests of all stakeholders by making decisions and building policy framework processes that fulfill the stakeholders’ needs. As far as Islamic corporate governance (ICG) is concerned, the institution of the Shari’ah board comes into the picture and plays a crucial role in favoring the interest of the stakeholders by ensuring that all corporation activities are in line with the Shari’ah principles. This paper attempts to examine the administrative relationships between the SB and other stakeholders by looking at the duties, roles, and responsibilities of the SB toward other stakeholders and vice versa in Brunei Darussalam. For this purpose, it relies on doctrinal and Islamic worldview methodologies and uses both content and legal analysis methods. After the discussion, it is concluded that the administrative relationship between the Shari’ah board and other stakeholders may take the form of imamah (ultimate authority), wilayah (specific authority), taʿlimiyah (educational), or istishariyah (consultative) relationship, depending on the type of relevant stakeholder. Nonetheless, to align the administrative relationship between SB and other stakeholders with these notions, further legal and regulatory amendments need to be made to the Bruneian Shariah governance framework.